Accumulation of Nutrients in the Raw of Crambe L. Species - Vergun, Olena; Shymanska, Oksana; Rakhmetov, Dzhamal; Fishchenko, Valentyna; Bondarchuk, Oleksandr; Rakhmetova, Svitlana (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2019)
Investigation of accumulation of different compounds in above-ground part of these plants an important aspect for evaluation of perspective of use. The aim of this study was to compare the peculiarities of the biochemical composition of Crambe species dynamically. Plant material collected from the experimental collection of M.M. Gryshko National Botanical Garden of the NAS of Ukraine. It was studied above-ground parts of C. cordifolia Steven, C. koktebelica (Junge) N.Busch, C. maritima L., C. steveniana Rupr. At the spring vegetation, budding stage, flowering, and fruitage. Following biochemical parameters was studied: dry matter by drying to consist weight at the 105 °C; content of sugars by Bertrand’s method using of glucose scale; ascorbic acids with 2.6-dichlorophenolindophenol, tannins with indigo carmine discoloration, organic acids by sodium hydroxide titration with phenolphthalein; carotene with gasoline galosh spectrophotometrically; ash in muffle over. The dry matter during vegetation was from 9.76 (C. cordifolia, budding) to 22.54 (C. maritima at the fruitage) %, total content of sugars from 6.54 (C. maritime at the fruitage) to 33.18 (C. cordifolia at the budding) %, ascorbic acid from 139.85 (C. maritima at the spring vegetation) to 987.02 (C. maritime at the budding) mg%, ß-carotene from 0.39 (C. maritima at the budding) to 1.82 (C. cordifolia at the fruitage) mg%, tannins from 1.28 (C. cordifolia at the fruitage) to 7.47 (C. steveniana at the budding) %, content of organic acids from 3.12 (C. steveniana at the fruitage) to 6.28 (C. koktebelica at the spring vegetation) %, ash from 6.11 (C. maritima at the spring vegetation) to 14.61 (C. cordifolia at the flowering) %. Correlation analysis showed that between the content of tannins and organic acids existed positive moderate correlation (r = 0.52). Between other parameters found the weak, very weak positive or negative correlation. Thus, comparing biochemical analyze identified that raw of four species of Crambe is a valuable source of nutrients during vegetation. The high content of sugars, ascorbic acid, and carotene can recommend these plants as forage crops. Also, raw of these plants can be recommended for farther pharmacological investigations.